Research indoor radio propagation models for design survivability security systems built on the ZIGBEE standard - Родін, Сергій Олександрович (Ukrainian Information Security Research Journal, 2015)
In this article describes the main types of radio propagationmodels and expediency of the application of thesemodels for the simulation is substantiated. The knownindoor radio propagation models are considered, that is:OSM (one-slope model), model Keenan-Motley, COST231 Multi-Wall Model. The theoretical calculations basedon these models are conducted. The method and meansof experimental research radio propagation of ZigBeestandard are described. The results of experimental researchwas conducted and have been compared with theoreticalcalculations of the signal attenuation. The combinedresults of the research are processed and analyzed.The suitability of known models for the design of a wirelesssecurity system, built on the standard ZigBee is verified.A new approach for the design and simulation ofwireless systems, which can improve their characteristicssuch as reliability and survivability was proposed.